Short‐ and Long‐Term Variations in the Reykjanes Geothermal Reservoir From Seismic Noise Interferometry. Issue 11 (4th June 2019) - Sánchez‐Pastor, Pilar; Obermann, Anne; Schimmel, Martin; Weemstra, Cornelis; Verdel, Arie; Jousset, Philippe
Abstract: The Reykjanes Geothermal System (RGS) is a high‐temperature geothermal system located on the Reykjanes peninsula, a transtensional plate‐boundary zone located on the southwestern tip of Iceland. The area is characterized by high seismicity, recent volcanism, and high‐temperature geothermal fields. We use seismic noise records from April 2014 to August 2015 to study stress changes and potential deformation of the subsurface caused by injection and production operations at RGS through seismic interferometry. We retrieve continuous time series of waveform similarity values and seismic velocity changes during this period. The S‐transform of the similarity values allows us to clearly identify three variations in the mechanical properties of the Reykjanes peninsula related to rapid changes of RGS production. In addition, we observe a slow seismic velocity decrease of 0.36%/year in the reservoir due to the water deficit and seasonal variations associated with the energy production demand. Plain Language Summary: The Mid‐Atlantic Spreading Ridge divides the Reykjanes peninsula into two tectonic plates and causes the high volcanic activity that characterizes the area. The Reykjanes Geothermal System is one of the five high‐temperature geothermal systems exploited in this peninsula. The energy production of Reykjanes Geothermal System has been increasing, causing drastic changes in reservoir conditions, such as, a man‐made subsidence of around 10 cm in the area. We employ three current methodologies to monitor changes of mechanical and structural properties in the subsurface, using 1.5 years of continuous seismic records. We identify and locate three short‐term variations associated with abrupt injection and production rate changes in Reykjanes Geothermal System. In addition, we observe a slow seismic velocity decrease due to the long‐term water extraction, as well as variations associated with demand‐driven seasonal fluctuations in the extraction rates. Key Points: Identification of three elastic properties changes in time‐frequency associated with abrupt injection and production rate variations Water deficit in the reservoir leads to a gradual seismic velocity decrease Seasonal production rate variations within the geothermal reservoir are observed as structural property changes